(untitled) (Journal of Universal Science Research, 2025)
This article contains information about the social system depicted in Animal Farm, including ideas about equality and its impact on society. By examining the changing power dynamics among the animals and their consequences, we understand how Orwell represents the fragility of social justice and the ongoing struggle for equality.